Nonrenewable resources, strategic behavior and the hotelling rule: An experiment - Roel van Veldhuizen; Joep Sonnemans (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
This study uses the methods of experimental economics to investigate possible reasons for the lack of empirical support for the Hotelling rule for nonrenewable resources. We argue that as long as resource stocks are large enough, producers may choose to (partially) ignore the dynamic component of their production decision, shifting production to the present and focusing more on strategic behavior. We experimentally vary stock size in a nonrenewable resource duopoly setting and find that producers with large stocks indeed pay significantly less attention to variables related to dynamic optimization, and overproduce relative to the Hotelling rule.
Keywords: C90; Q30; L13; 330; laboratory experiment; nonrenewable resources; Hotelling rule; dynamic oligopoly